Pemanfaatan Limbah Cangkang Kepiting sebagai Bahan Penambahan Pakan Ternak Berkalsium Tinggi dalam Tinjauan Moderasi Beragama - Alliffia Balqis Candharaning Ratri (UIN Raden Mas Said Surakarta, 2021)
Crab creation is often found in Pantai Beringin Village, Sulamu District, Kupang Regency, East Nusa Tenggara. In one day, Pantai Beringin Village is able to collect 200 kilograms of crabs, on the other hand, 150 kilograms or 75% of the total are shells. Crab shells that are not used become waste that has been piled up for years and even thrown away. Meanwhile this village has a crab shell grinding machine, but it is not operational. Meanwhile, crab shells have as much as 70% chitin, so they are very good to use as a basic ingredient for making animal feed. Chitin, like an addictive feed, can also improve the nutritional quality of animal feed. To empower residents in utilizing shells, the approach used is ABCD (Asset Based Comminity-driven Development). This procedure uses the legacy of the existing community, with a focus on the main issue of using crab shell waste. The results of this processing are submitted to BUMDes and their marketing management. With the diversity of religions that exist in Pantai Beringin Village, it cannot be separated from